Endothelin ETB receptors contribute to sex differences in blood pressure elevation in angiotensin II hypertensive rats on a high‐salt diet1. (28th May 2013) - Kittikulsuth, Wararat; Looney, Stephen W; Pollock, David M
Summary Female rats are more resistant to blood pressure increases induced by high salt (HS) intake or angiotensin (Ang) II infusion. Because endothelin ETB receptors on endothelial and epithelial cells mediate tonic vasodilation and sodium excretion, we hypothesized that ETB receptors limit the hypertensive response and renal injury induced by HS diet alone or with chronic AngII infusion (AngII/HS) in female compared with male rats. A 4 week HS diet (4% NaCl) did not significantly change blood pressure (measured by telemetry) in either male or female Sprague‐Dawley rats. Administration of the ETB receptor antagonist A‐192621 (1, 3 and 10 mg/kg per day in food) during HS feeding caused a dose‐dependent increase in blood pressure in both sexes. In AngII/HS rats, males had a larger increase in blood pressure than females. The increase in blood pressure produced by ETB receptor blockade in male AngII/HS rats was not significant. However, A‐192621 treatment resulted in a significant further increase in blood pressure in female AngII/HS rats. Male rats had consistently higher protein excretion rates before and during AngII/HS, but this was not significantly affected by ETB receptor blockade in either sex. In conclusion, ETB receptors play a significantly greater beneficial role in protecting female compared with male rats against AngII‐induced hypertension and may contribute to the sex differences in AngII‐induced hypertension.